1996
DOI: 10.2337/diacare.19.2.112
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effect of Cigarette Smoking on Glucose Tolerance and Other Cardiovascular Risk Factors

Abstract: Smoking acutely impaired glucose tolerance and insulin sensitivity, enhanced serum cholesterol and triglyceride levels, and raised blood pressure and heart rate. These findings support the pathogenetic role of cigarette smoking on cardiovascular risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
127
5
4

Year Published

1999
1999
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(149 citation statements)
references
References 0 publications
13
127
5
4
Order By: Relevance
“…Chiolero et al 12 reported that in healthy men, chronic smoking is associated with increased insulin levels, independent of other factors known to influence the sensitivity to this hormone. Although serum cortisol did not increase in most patients evaluated in this study, other authors have shown that smoking increases circulating levels of this hormone and others such as catecholamines, and growth hormone actions that are antagonistic to insulin and may contribute to insulin resistance and higher blood glucose levels between smokers 28,36 . Excess abdominal fat may also explain the occurrence of IR, since the present study showed a correlation between insulinemia and WC.…”
Section: Discussioncontrasting
confidence: 58%
“…Chiolero et al 12 reported that in healthy men, chronic smoking is associated with increased insulin levels, independent of other factors known to influence the sensitivity to this hormone. Although serum cortisol did not increase in most patients evaluated in this study, other authors have shown that smoking increases circulating levels of this hormone and others such as catecholamines, and growth hormone actions that are antagonistic to insulin and may contribute to insulin resistance and higher blood glucose levels between smokers 28,36 . Excess abdominal fat may also explain the occurrence of IR, since the present study showed a correlation between insulinemia and WC.…”
Section: Discussioncontrasting
confidence: 58%
“…As for the effects of smoking on diabetes, laboratory studies have indicated that cigarette smoking causes insulin resistance in peripheral tissues, whereas insulin secretion may be unimpaired or somewhat overstimulated [27±30]. In an experimental control trial using two oral glucose tolerance tests, smoking acutely impairs glucose tolerance and acutely increases serum insulin and Cpeptide concentrations [31]. Cigarette smoking is also known to stimulate the release of counter-regulatory hormones and consequently cause temporary increase in plasma glucose concentrations [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Cigarette smoking is another potential confounder since it may cause acute insulin resistance (Attvall et al 1993;Frati et al 1996). Intake of dietary RS on the day before a meal challenge may improve glucose tolerance (Robertson et al 2002).…”
Section: Subject Preparationmentioning
confidence: 99%